Optimizing Income Tax Exemption: A Focus on the 'Subsistence Minimum' Threshold: Pembebasan dari Pajak Penghasilan pada Tingkat 'Kebutuhan Hidup Minimum' - Sabirov, Mirza Kylichbayevich (Universitas Muhammadiyah Sidoarjo, 2024)
This article delves into the establishment of a perspective on introducing non-taxable income for individuals, emphasizing the effective organization of tax relations. Employing a rigorous research methodology, the study aims to provide conclusive insights, scientific recommendations, and practical guidance. The goals encompass fostering a deeper understanding of non-taxable income implications, while the methods involve a comprehensive examination of tax reforms, benefits, and personal income taxation. The results offer valuable perspectives on optimizing taxation systems, particularly in relation to the subsistence minimum. The implications of this research extend to informing global tax policies, promoting efficiency, and ensuring equitable fiscal practices. Highlights: The article explores the introduction of non-taxable income, addressing key issues in tax relations. It provides conclusive insights, scientific proposals, and practical recommendations for optimizing taxation systems. The research emphasizes the importance of fostering equitable fiscal practices and informing global tax policies. Keywords: Tax Relations, Tax-Free Income of Individuals, Personal Income Tax, Property Tax, Fiscal Practices